2021
DOI: 10.3389/fmars.2021.632243
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Windfarm Footprint of Sediment Organic Matter Mineralization Processes

Abstract: Offshore windfarms (OWFs) offer part of the solution for the energy transition which is urgently needed to mitigate effects of climate change. Marine life has rapidly exploited the new habitat offered by windfarm structures, resulting in increased opportunities for filter- and suspension feeding organisms. In this study, we investigated the effects of organic matter (OM) deposition in the form of fecal pellets expelled by filtering epifauna in OWFs, on mineralization processes in the sediment. OM deposition fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Physical disturbance of the seabed which resuspends near-surface sediments into the oxic water column will recycle labile organic carbon into the ocean and potentially impact the atmospheric carbon system (Sala et al, 2021), although it can also simply re-distribute and redeposit sediments (Rijnsdorp et al, 2021). Seabed disturbance impacts the benthic faunal community, which plays a key role in the biogeochemical processes determining what fraction of deposited carbon is recycled (remineralized) or buried (stored) (de Borger et al, 2021a;de Borger et al, 2021b).…”
Section: Anthropogenic Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical disturbance of the seabed which resuspends near-surface sediments into the oxic water column will recycle labile organic carbon into the ocean and potentially impact the atmospheric carbon system (Sala et al, 2021), although it can also simply re-distribute and redeposit sediments (Rijnsdorp et al, 2021). Seabed disturbance impacts the benthic faunal community, which plays a key role in the biogeochemical processes determining what fraction of deposited carbon is recycled (remineralized) or buried (stored) (de Borger et al, 2021a;de Borger et al, 2021b).…”
Section: Anthropogenic Pressuresmentioning
confidence: 99%
“…Bottom trawling is the most spatially significant anthropogenic process physically disturbing shelf sediments (Oberle, et al, 2016b;Rijnsdorp et al, 2021), while wind farms have been shown to locally increase organic matter deposition (and recycling) because of faunal colonization of their structure (de Borger et al, 2021a). Other activities, including pipe and cable laying, aggregate extraction, and dredge disposal, are also expected to impact organic matter storage and deposition, although their impacts are more spatially restricted.…”
Section: Anthropogenic Pressuresmentioning
confidence: 99%
“…This new epifaunal colonization leads to a significant transfer of organic carbon (OC) in the form of fecal pellets and biomass sinking from the structures onto the sediments surrounding the wind turbines (Krone et al, 2013;De Borger et al, 2021;Mavraki et al, 2022). Using a 3D hydrodynamic model developed by Ivanov et al (2021); De Borger et al (2021) found that this leads to a 10-11% increase in OC accumulation in the upper 10 cm of the sediment and an increase in anoxic mineralization processes in the vicinity of the OWFs. As a result, the OWFs installed on the sediments of the Belgian Part of the North Sea became local carbon sinks compared to the baseline scenario (areas without OWFs) and have increased the total amount of OC in the upper 10 cm of the sediment by 28,715 tons (De Borger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The effects on local benthic habitats during installation works and operations of offshore wind farms (OWFs) are of a complex nature and extend both below and above the surface of the sea. Previous studies have shown that OWFs can impact areas through the introduction and spread of alien species (De Mesel et al, 2015;Wilhelmsson and Malm, 2008), affect organic matter deposition (De Borger et al, 2021) and carbon assimilation (Mavraki et al, 2020), and alter community structures (Coates et al, 2014;Hutchison et al, 2020;Wilhelmsson and Malm, 2008) through the loss of soft-sediment habitats and the subsequent introduction of artificial hard-bottom substrates. The newly created habitat is usually larger than the lost habitat (Wilson and Elliott, 2009).…”
Section: Introductionmentioning
confidence: 99%